Kinematic Analysis and Motion Simulation of a 2D Cable Robot Designed for Greenhouse Applications - Hassan Masoudi; Ali Madadi Kahkesh (Biomechanism and Bioenergy Research)
The high adaptability of cable robots to complex environments has led entrance of these types of robots into the agricultural sector in recent years. Kinematic and dynamic modelling of robots is essential to develop the control algorithms and optimize their movement. In this research, the kinematic analysis of a two-dimensional laboratory cable robot, which is being developed for agricultural applications, and the results of its movement simulation in Simscape Multibody environment of MATLAB software are presented. The motions simulation of the robot in reaching a hypothetical point and traveling a certain path have been done using PID controller. Before the final evaluation, the controller used to control the robot was adjusted, so that the robot shows a suitable and acceptable performance in terms of control indicators. Finally, the time response graphs of the robot in the states of reaching a hypothetical point and traveling a linear path were determined and analyzed. The values of rise time, peak time, overshoot, and steady state error at reaching point (40, 30) were 0.8 s, 2.3 s, 10-20 %, 0 respectively. Also, the peak time and overshoot values at traveling a linear path in X direction were 2.1 s and 50%, respectively. According to the simulation results, the designed robot behaved well in reaching a hypothetical point and traveling a certain path.